Short history of Biology from the origins to the 20th Century - Simonetta, Alberto Mario (Manuali - Scienze, 2003)
The book tells the story of the development of both knowledge and theories about the living organisms since Antiquity until the beginning of the 20th century. It also endeavours to link the advances in sciences and the events in the life of scientists with the historical and social framework within which they lived. When possible some hints have been provided about the personalities of the scientists themselves. It is especially meant both for biologists and naturalists, but an attempt has been made to make it interesting reading also for any layman with an interest in history and sciences.